Protection of human rights - relations between legal orders: national, EU, ECHR - Menard, Maja (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2019)
The protection of human rights is characterised by the substantive fragmentation of the law, within the framework of which an integrational interaction between national and supranational orders drives the evolution of the substantive human rights law. At the same time, the institutional proliferation provides the users of the system with strategic institutional choices for the maximisation of their interests. Neither characteristic is subject to a realistic threat of a conflict between different norms or institutions that could jeopardise the system or, more importantly, the content of the protection.
Keywords: Constitution; Court of Justice of the European Union; človekove pravice; European Convention on Human Rights; European Court of Human Rights; European Union; Evropska konvencija o človekovih pravicah; Evropska unija; Evropsko sodišče za človekove pravice; fragmentacija mednarodnega prava; fragmentation of international law; human rights; nacionalno sodišče; national court; Sodišče Evropske unije; Ustava